EVALUATION OF SERVICE QUALITY TO INCREASE CUSTOMER SATISFACTION AT UMKM RESTAURANT YOI - Suranto Suranto; Agus Marimin; Indra Lila Kusuma; Desy Nur Pratiwi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
Satisfaction towards customers or consumers is one of the success factors in running a business, therefore customers or consumers must get excellent service. This study aims to evaluate and identify the sevice quality so as to increase customer satisfaction. The benefits of research are feedback, recommendations and implementation of improving service quality in the service sector, Yoi restaurant. Data collection methods are through questionnaires, observation, documentation and literature study. Analysis method is through service quality to analyze consumer perceptions and expectations. Based on the analysis, the level of service quality at the restaurant is unsatisfactory.